A study of foreign funded missionary non-government organizations (NGOs) in Bangladesh - Banu, Nusrat Jabeen (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.